Coseismic Throw Variation Across Along‐Strike Bends on Active Normal Faults: Implications for Displacement Versus Length Scaling of Earthquake Ruptures. Issue 11 (9th November 2018) - Iezzi, Francesco; Mildon, Zoë; Walker, Joanna Faure; Roberts, Gerald; Goodall, Huw; Wilkinson, Maxwell; Robertson, Jennifer
Abstract: Fault bends, and associated changes in fault dip, play a key role in explaining the scatter in maximum offset versus surface rupture length fault scaling relationships. Detailed field measurements of the fault geometry and magnitude of slip in the 2016–2017 Central Italy earthquake sequence, alongside three examples from large historical normal‐faulting earthquakes in different tectonic settings, provide multiple examples in which coseismic throw increases across bends in fault strike where dip also increases beyond what is necessary to accommodate a uniform slip vector. Coseismic surface ruptures produced by two mainshocks of the 2016–2017 Central Italy earthquake sequence (24 August 2016 Mw 6.0 and 30 October 2016 Mw 6.5) cross a ~0.83‐km amplitude along‐strike bend, and the coseismic throws for both earthquakes increase by a factor of 2–3, where the strike of the fault changes by ~28 o and the dip increases by 20–25 o . We present similar examples from historical normal faulting earthquakes (1887, Sonora earthquake, Mw 7.5; 1981, Corinth earthquakes, Mw 6.7–6.4; and 1983, Borah Peak earthquake, Mw 7.3). We demonstrate that it is possible to estimate the expected change in throw across a bend by applying equations that relate strike, dip, and slip vector to horizontal strain conservation along a nonplanar fault for a single earthquake rupture. The calculated slip enhancement in bends can explain much of the scatter in maximum displacement ( Dmax ) versus surface rupture length scaling relationships. If fault bends are unrecognized, they can introduce variation in Dmax that may lead to erroneous inferences of stress drop variability for earthquakes, and exaggerate maximum earthquake magnitudes derived from vertical offsets in paleoseismic data sets. Key Points: In throughgoing normal fault ruptures, such as the 2016 central Italy earthquakes, throw maxima occur at fault bends Fault growth and linkage result in steeper dips within bends, conservation of strain along strike results in throw maxima across bends Enhanced slip at bends contributes to scatter in fault scaling relationships and overestimation bias of magnitude, moment and stress drop